2012
DOI: 10.1007/s11886-012-0289-3
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation and Mortality in Patients with Acute Myocardial Infarction: A Systematic Overview and Meta-analysis

Abstract: Atrial fibrillation (AF) confers an increased risk of mortality in patients hospitalized for acute myocardial infarction (AMI). However, it is unclear whether new-onset and preexisting AF portend a different risk. We extracted data from studies that evaluated in-hospital mortality in patients with AMI and included information on cardiac rhythm. Overall, the risk of mortality was higher in patients with AF than in those in sinus rhythm (OR 2.00, 95 % CI: 1.93-2.08; P < 0.0001). Compared with patients who remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
53
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 54 publications
9
53
0
8
Order By: Relevance
“…However, controversy exists whether AF carries a different mortality risk in ACS versus stable CAD [11,12,[19][20][21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, controversy exists whether AF carries a different mortality risk in ACS versus stable CAD [11,12,[19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Second, non-fatal bleeding, occurring at an annual rate between 3% and over 15% in the spectrum of warfarin monotherapy, dual antiplatelet therapy, their combinations and TT, have been shown to affect late mortality [23]. Perhaps most importantly, cardiovascular risk factors and co-morbidities, measured and unmeasured, may contribute to worse prognosis [2,5,11,19,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Так, например, данные международного регистра GRACE показывают, что у пациентов с ОКС как с предсуществующей, так и с вновь возникшей ФП значительно выше госпитальная летальность (14,5% и 8,9%, соответственно), чем у пациентов без ФП (1,2%) [2]. Результаты мета-анализа исследований с ОКС показали, что риск госпитальной смерти у пациентов с ФП на ЭКГ был в 2 раза выше, чем у пациентов с синусовым ритмом (относительный риск 2,00; 95% доверительный интервал 1,93-2,08; р<0,0001) [3].…”
Section: материал и методыunclassified
“…the independent predictors of death after discharge from hospital up to 12 months from ACs onset were the baseline hemoglobin <110 g/L (oR 16,00; 95% Ci 2,57-99,50; р=0,003), non-treatment by antithrombotics before ACs (oR 7,22; 95% Ci 2,20-23,68; р=0,001), hospital risk by GRACe >140 pts. (oR 6,88; 95% Ci 1,44-32,80; р=0,015) and non-prescription of aspirin in discharge (oR 3,21; 95% Ci 1,61; р=0,02). Conclusion.…”
mentioning
confidence: 99%
“…Few published studies have been conducted regarding this question and the results are conflicting. 2,5---11 In a recent meta-analysis, Angeli et al 12 showed that AF in the setting of AMI was associated with a two-fold higher risk of in-hospital mortality, but the risk of death was 87% higher in patients with new-onset AF than in those with permanent AF.…”
Section: Introductionmentioning
confidence: 99%